Estimated changes in carbon stock due to changes in land use around Yogyakarta International Airport - Utami, Westi; Sugiyanto, Catur; Rahardjo, Noorhadi (Brawijaya University, 2024)
Land use plays an important role in maintaining carbon stock balance, ecosystem sustainability, and the environment. Massive land use changes in forest areas, peatlands, mangroves, and greenways result in an increase in CO2 release. This research aimed to analyze the impact of land use changes on the value of the carbon stock around Yogyakarta International Airport. The data used were Pleiades images in 2014, 2018, and 2022. Image analysis was carried out visually to produce detailed and accurate land use classification. Meanwhile, multitemporal map overlays were carried out to find out land use changes. Changes in carbon stock were obtained from the land use formula multiplied by the value of the Greenhouse Gas Constant (GGC). The results showed that the construction of an airport and its supporting infrastructure triggered land use changes that had implications for the decreasing carbon stock. The decrease in the area of vegetation cover in fields, community plantations, and mixed plantations from 2014 to 2022, amounting to -640.99 ha, increased carbon emissions. The results of the analysis showed that there had been changes in carbon stock. In 2014, the value was 150,286.57 t C/ha; in 2018, it decreased to 136,631.56 t C/ha; and in 2022, it reduced to 133,554.36 t C/ha. Massive economic activity and infrastructure development trigger reduced vegetation cover, resulting in increased carbon and increased carbon being released into the atmosphere. The problem of land conversion that affects changes in carbon stock and impacts climate change requires mitigation, among which is proper land use management and sustainable spatial planning.